Nivel de satisfacción del usuario con cáncer en relación a la aplicación de los principios bioéticos de la enfermera (o) - Florian Avila, Martha Melissa (2010)
This study is a descriptive – correlational research and cross section. It was made with cancer users in services of Medicine, Surgery and Gynecology from Hospital Belen from Trujillo during the months of March-May 2010, in order to determine the relationship between satisfaction level of hospitalized cancer users with the application of the bioethical principles of the nurse(o).The sample universe consisted of 70 users who who obey the incorporation criteria. The information was obtained through the following instruments: Satisfaction Perceived by Hospitalized users and application of the Bioethical Principles of the Nurse (o)”, valid and reliable, implemented through a personal interview, considering the rights of anonymity, free participation and confidentiality. The results were presented in graphs and statistical tables in uni dimensional and bi-dimensional charts and graphics, which reported that the highest percentage correspond to that users who are satisfied with the care offered, and satisfied with the application of bioethical principles. For the statistical analysis was applied the Test of Independence of Criteria (Chi - Cuadrado), that reported that there are high significance between satisfaction level in cancer users in relation to the application of the bioethical principles of the nurse.